2023
DOI: 10.1002/ajum.12347
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound: A comparison of image interpretation accuracy between curvilinear and phased array transducers

Abstract: IntroductionBoth curvilinear and phased array transducers are commonly used to perform lung ultrasound (LUS). This study seeks to compare LUS interpretation accuracy of images obtained using a curvilinear transducer with those obtained using a phased array transducer.MethodsWe invited 166 internists and trainees to interpret 16 LUS images/cineloops of eight patients in an online survey: eight curvilinear and eight phased array, performed on the same lung location. Images depicted normal lung, pneumothorax, ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There are reasons why operators may prefer one over the other, such as rib spaces or frequency, but many regard them as interchangeable. Walsh et al 3 . undertook an experiment where they asked internists and trainees to interpret lung ultrasound performed with both transducers and found that for expert readers, no difference in accuracy was seen, but for novice readers, the curvilinear transducer led to higher accuracy.…”
mentioning
confidence: 99%
“…There are reasons why operators may prefer one over the other, such as rib spaces or frequency, but many regard them as interchangeable. Walsh et al 3 . undertook an experiment where they asked internists and trainees to interpret lung ultrasound performed with both transducers and found that for expert readers, no difference in accuracy was seen, but for novice readers, the curvilinear transducer led to higher accuracy.…”
mentioning
confidence: 99%